Case Report: Streptococcus Suis Meningitis Diagnosed in a HIV-Infected Patient With Cryptococcal Meningitis Using Next-Generation Sequencing - Xie, Yirui; Ruan, Bing; Lang, Guanjing; Zhu, Biao (Frontiers in Medicine, 2021)
Background: Streptococcus suis has been recognized as a zoonotic pathogen that may cause infections in humans. Although rarely described, it is not surprising that both cryptococcal and streptococcus suis meningitis infections can co-exist in a HIV-infected patient with a low CD4 count. However, a fast and accurate diagnose of meningitis of multipathogenic infections is challenging. In this report, we describe such a case of a HIV-infected patient with meningitis of multipathogenic infections. Case Presentation: The patient was a 34-year-old Chinese male who was diagnosed with cryptococcal meningitis and HIV at the same time about one year ago. During the same time period, he had received (with good compliance) fluconazole and tenofovir-lamivudine- dolutegravir based antiretroviral therapy (ART). However, symptom of progressively worsening occipital headache appeared after he was exposed to a truck which was used for transporting pigs. Initial workup indicated an increase of the cerebrospinal fluid (CSF) opening pressure (OP) and an increase in the number of lymphocytes and proteins in CSF. A magnetic resonance imaging (MRI) scan revealed that partial cerebellar surface enhancement. The cryptococcus capsular antigen test of CSF was positive. The results of the India Ink microscopy for cryptococcus, nucleic acid of CMV and EBV and mycobacterium tuberculosis (MTB) tests of CSF were negative. The results of the bacteria and fungi smear and culture of CSF were also negative. Eventually, streptococcus suis was detected using next-generation sequencing (NGS) in CSF. The diagnosis of Streptococcus suis meningitis was made based on the patient’s contact history with carrier pigs and the clinical findings addressed above. The treatment of two weeks of intravenous ceftriaxone and one week of oral moxifloxacin resulted in improvement of the condition of CSF. The anti-fungal treatment using fluconazole continued until the CFS OP went down to a normal level and the cryptococcus capsular antigen test of CSF was negative six months later. Conclusion: This case highlights that NGS might be beneficial to HIV-infected patients who have meningitis with negative CSF culture results. Multiple etiologies for such condition in the immunocompromised patients must be taken into consideration and early stage NGS is recommended.